(untitled) (International Journal of Food and Nutritional Sciences, 2026)
Background: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder marked by cognitive impairment, cholinergic dysfunction, oxidative stress, and neuroinflammation. Persea americana (avocado) is rich in bioactive compounds with antioxidant and neuroprotective properties. Objective: To evaluate the neuroprotective effects of Persea americana in a scopolamine-induced Alzheimer’s disease model in rats. Methods: Cognitive impairment was induced in Wistar rats using scopolamine. Animals were treated with Persea americana extract at different doses. Behavioral tests, biochemical assays, and histopathological analyses were conducted. Results: Treatment significantly improved memory and learning, reduced oxidative stress, inhibited acetylcholinesterase activity, and attenuated neuronal damage. Conclusion: Persea americana exhibits significant neuroprotective effects and may serve as a potential therapeutic agent for Alzheimer’s disease.